2016
DOI: 10.1002/rnj.225
|View full text |Cite
|
Sign up to set email alerts
|

The Competency Model for Professional Rehabilitation Nursing

Abstract: Background: Rehabilitation nursing is practiced in various settings along the healthcare continuum. No framework is noted in the literature that defines the necessary competencies of the rehabilitation nurse. Purpose: To develop a Competency Model for Professional Rehabilitation Nursing and its application to clinical and educational practice. Method/design: A seven-member Association of Rehabilitation Nurses (ARN) task force was convened; conducted a literature review, reviewed current and historical ARN docu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
109
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(118 citation statements)
references
References 35 publications
1
109
0
4
Order By: Relevance
“…In summary, the role of the nurse in rehabilitation as outlined by ARNA (2004), Long et al (2002), Vaughn et al (2015), and Pryor and Smith (2002) articulates similarities in that nurses assist patients to achieve their rehabilitation goals through teaching, coaching and support during their everyday practice. Furthermore, nurses have a significant role in the coordination and oversight of care and ensuring quality of care, in addition to advocacy, communication and emotional support to patients and families.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, the role of the nurse in rehabilitation as outlined by ARNA (2004), Long et al (2002), Vaughn et al (2015), and Pryor and Smith (2002) articulates similarities in that nurses assist patients to achieve their rehabilitation goals through teaching, coaching and support during their everyday practice. Furthermore, nurses have a significant role in the coordination and oversight of care and ensuring quality of care, in addition to advocacy, communication and emotional support to patients and families.…”
Section: Introductionmentioning
confidence: 99%
“…They play a key role in promoting successful transitions by developing and evaluating the transition plan and identifying and communicating barriers to the plan. 14 Examples of barriers include limited finances to cover out-ofpocket costs of PAC and family members who do not have the capacity to provide care post discharge. Communicating this information to the interprofessional team early in the patient's hospital stay is essential to assure that the transition plan is tailored to the needs of the patient and family, and that patients are transferred to the appropriate PAC setting.…”
mentioning
confidence: 99%
“…Hurley et al (1997) stated that the various methods of factor analysis each have their strengths and weaknesses, but the choice of which one to use depends on a study's requirements and context. When reviewing similar research studies, different investigators have identified professional nursing competencies mostly via factor analysis: ethical values and attitudes; general clinical skills and caring; personal and professional development; clinical biomedicine; critical thinking; communication/coordination; management/teaching; interpersonal relationships; and nursing research (Clinton, Murrells, & Robinson, 2005;Hartigan, Murphy, Flynn, & Walshe, 2010;Hsu & Hsieh, 2013;Lee-Hsieh, Kao, Kuo, & Tseng, 2003;Lofmark, Smide, & Wikblad, 2006;Nilsson et al, 2014;Numminen, Meretoja, Isoaho, & Leino-Kilpi, 2013;Vaughn et al, 2016).…”
Section: Items/competencies Q28mentioning
confidence: 99%